2016
DOI: 10.18632/oncotarget.10421
|View full text |Cite
|
Sign up to set email alerts
|

Metformin as a new anti-cancer drug in adrenocortical carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare heterogeneous malignancy with poor prognosis. Since radical surgery is the only available treatment, more specific and effective drugs are urgently required. The anti-diabetic drug metformin has been associated with a decreased cancer prevalence and mortality in several solid tumors, prompting its possible use for ACC treatment.This paper evaluates the in vitro and in vivo anti-cancer effects of metformin using the ACC cell model H295R.Metformin treatment significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…Metformin inhibits EMT at the range of 2.5–50 mM in different cell lines [6, 17, 18, 25, 26]. We used 10 mM metformin in our study, which is around 200-fold higher than the plasma level of metformin in type 2 diabetic patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin inhibits EMT at the range of 2.5–50 mM in different cell lines [6, 17, 18, 25, 26]. We used 10 mM metformin in our study, which is around 200-fold higher than the plasma level of metformin in type 2 diabetic patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous preclinical in vivo (4,6,12,27,28) and in vitro (5,7-9,14,29) cancer models have provided evidence of metformin's anti-tumorigenic potential, which is commonly attributed to indirect whole-body effects (insulin-dependent) and/or direct (insulin-independent) effects (30). Metformin has been shown to reduce hyperinsulinemia and glycemia thereby reducing tumor cell insulin receptor (IR) expression and downstream signaling (30).…”
Section: Discussionmentioning
confidence: 99%
“…Even though metformin has been used mainly as a first‐line drug for the treatment of type 2 diabetes, the results from a number of large‐scale epidemiologic and laboratory studies suggest that metformin may also exert anticancer effects through a different mechanism . Due to the rarity of gallbladder carcinoma, no data are currently available regarding cancer prevalence and metformin treatment in patients with GBC, nor is there evidence on the concrete effects of metformin on tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Even though metformin has been used mainly as a first-line drug for the treatment of type 2 diabetes, the results from a number of large-scale epidemiologic and laboratory studies suggest that metformin may also exert anticancer effects through a different mechanism. (23) Due to the rarity of gallbladder carcinoma, no data are currently available regarding cancer prevalence and metformin treatment in patients with GBC, nor is there evidence on the concrete effects of metformin on tumor growth. In this study, we not only demonstrated that metformin is capable of inhibiting gallbladder cancer cell viability and inducing apoptosis by inhibiting the PI3K-Akt axis and the Bcl2 family but also revealed the regulatory roles of chloride intracellular channel 1 (CLIC1) in the resistance of GBC to metformin.…”
Section: Discussionmentioning
confidence: 99%